Ten big questions for higher education - Holmes, C; Mayhew, K; Keep, E (ESRC Research Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2012)
The dominant assumptions about the UK higher education (HE) system are simple: graduates earn more than non-graduates, graduates have skills that make them more productive and HE is a key driver of economic growth and international competitiveness. These assumptions logically lead to a simple policy prescription: encourage young people to go to university. The Coalition government has scrapped the target of a 50 per cent participation rate and shifted a larger share of the cost onto students, but remains reliant on HE as a mechanism for raising incomes, improving social mobility and boosting productivity. This Issues Paper sets out what we consider to be the important questions for HE. For all of these questions, there is an answer which fits neatly with the story set out above. However, for all of these answers there is either a long history of academic research which directly challenges them or a notable absence of research. This paper aims to stimulate more open-minded debate.